If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -2(3 + -1a) = 4a 3a + (3 * -2 + -1a * -2) = 4a 3a + (-6 + 2a) = 4a Reorder the terms: -6 + 3a + 2a = 4a Combine like terms: 3a + 2a = 5a -6 + 5a = 4a Solving -6 + 5a = 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. -6 + 5a + -4a = 4a + -4a Combine like terms: 5a + -4a = 1a -6 + 1a = 4a + -4a Combine like terms: 4a + -4a = 0 -6 + 1a = 0 Add '6' to each side of the equation. -6 + 6 + 1a = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 1a = 0 + 6 1a = 0 + 6 Combine like terms: 0 + 6 = 6 1a = 6 Divide each side by '1'. a = 6 Simplifying a = 6
| x^2+6X=75 | | 2(2x+1)=x-5 | | 5-2(x-2)=x | | 2x(4+3x)=9 | | 5=4y-21 | | (6+3i)/(2-3i) | | 7y-1-2y=14 | | X^2+4X=175 | | 2(9x-1)+7(x+6)=60 | | 8x/6=7 | | 5/x=4/2x+10 | | 5/x=4/x+3 | | 6x/8=23 | | 18x/92=42 | | -18+-10=-3 | | 6p^2=36p+30 | | 13x/38=31 | | 13x*38=31 | | 4tsquared-5t+7=0 | | 10x*18=25 | | 30x-64=36 | | x^2-6x+y^2+5=0 | | 2x+15=46 | | 0.6/0.02= | | (11x*x)-1=(6x*x)+2 | | (-2x*x)=-32 | | 4x+14=28-2x | | 2y=6y | | (3x*x)-27=0 | | 121x^2-16/81 | | A(56)=630 | | A(34)=412 |